Circulating cell-free DNA of methylated insulin-like growth factor-binding protein 7 predicts a poor prognosis in hepatitis B virus-associated hepatocellular carcinoma after hepatectomy. (3rd April 2018) - Li, Feng; Qiao, Chen-Yang; Gao, Shuai; Fan, Yu-Chen; Chen, Long-Yan; Wang, Kai
Abstract: The initiation and progression of hepatocellular carcinoma (HCC) is a multistage process involving a variety of changes at the gene level. Methylation of insulin-like growth factor-binding protein 7 ( IGFBP7 ) plays a crucial role in HCC development. The main purpose of this study was to investigate the relationship between oxidative stress, DNA methyltransferases (DNMTs) expression, and IGFBP7 methylation, and to evaluate the prognostic value of serum IGFBP7 methylation status in patients with HCC after hepatectomy. We enrolled 155 patients with HCC undergoing surgical resection. The IGFBP7 methylation status, DNMTs mRNA levels and malondialdehyde (MDA), xanthine oxidase (XOD), reduced glutathione hormone (GSH), and glutathione-S-transferases (GST) levels were detected. MDA and XOD levels were significantly higher in IGFBP7 methylated group than unmethylated group, while GSH level was lower in methylated group than unmethylated group. The DNMT1 and DNMT3a mRNA levels were higher in IGFBP7 methylated group than unmethylated group. Kaplan–Meier curve analysis revealed that IGFBP7 promoter methylation was significantly correlated with overall survival (OS) ( p  < .001). Moreover, IGFBP7 methylation was an independent prognostic predictor for OS ( p  = .000) and early tumour recurrence (ETR) ( p  = .008) in HCC after hepatectomy. Our results indicated that IGFBP7 promoter methylation was associated with oxidative stress and DNMTs expression. Meanwhile, IGFBP7 promoter methylation was associated with OS and ETR, indicating that it might serve as a potentially independent prognostic factor in patients with HCC after hepatectomy.